Early clinical exposure to first year medical students through case-based learning in endocrine physiology - Bhattacharya, Srabani Nitish; Malgaonkar, Aniruddha Arjun; Kartikeyan, Sundaram (International Journal of Research in Medical Sciences, 2017)
Background:As per the Medical Council of India’s Vision-2015 document, coordinated inter-departmental efforts should be undertaken to provide early clinical exposure and to develop communication skills among medical students during the first year of Bachelor of Medicine, Bachelor of Surgery (MBBS) course. For this reason, this inter-departmental study was undertaken, to provide early clinical exposure while teaching endocrine physiology to first-year medical students. Case based learning (CBL) was used as an add-on to traditional didactic lectures (TDLs) for teaching endocrine physiology to first-year undergraduate medical students to compare the cognitive domain scores in pre CBL and post CBL tests. Methods: After getting permissions from the Institutional Ethics Committee (IEC) and other institutional authorities for conducting the study, the objectives of the study were explained to first year MBBS students. Written informed consent was taken from students (n=59) who were willing to participate in the study. After delivering regular TDLs on endocrine physiology as per topics in the syllabus, a pre CBL test was conducted. Subsequently, the participating students were simultaneously exposed to case scenarios related to the endocrine system by the same facilitator. A post CBL test (identical to pre CBL test) was administered to compare the cognitive domain scores. Results: Statistically significant differences were found in the student wise and question wise scores in the pre and post tests. Conclusions: Early clinical exposure of a relatively larger batch of students to CBL by the same facilitator was found to increase cognitive domain scores.